Kualitas Hasil Edamame pada Berbagai Umur Panen - Pebria Sisca; Dulbari Dulbari; Nurbani Kalsum (Politeknik Negeri Lampung, 2024)
Edamame is a type of soybean that is large in size and is harvested when it is still fresh and young. The fresh green color of edamame seeds and their sweet taste differentiate edamame soybeans from ordinary soybeans. The quality of edamame yields is one of the determining factors for the success of edamame cultivation. The aim of this research was to determine the physical quality, texture and level of damage to edamame at various harvest ages. The research was structured using a complete randomized block design with 5 treatments, each treatment having 4 replications. Research data were analyzed using ANOVA and tested by Fisher's LSD test at a significance level of 5%. The results of the research show that harvest age influences the texture, weight, size and level of damage to edamame pods. Based on the weight of the pods per plant, the best harvest age for edamame plants is 72 HST with a potential yield of 16.38 ton.ha-1, a texture value Edamame is a type of soybean that is large in size and is harvested when it is still fresh and young. The fresh green color of edamame seeds and their sweet taste differentiate edamame soybeans from ordinary soybeans. The quality of edamame yields is one of the determining factors for the success of edamame cultivation. The aim of this research was to determine the physical quality, texture and level of damage to edamame at various harvest ages. The research was structured using a complete randomized block design with 5 treatments, each treatment having 4 replications. Research data were analyzed using ANOVA and tested by Fisher's LSD test at a significance level of 5%. The results of the research show that harvest age influences the texture, weight, size and level of damage to edamame pods. Based on the weight of the pods per plant, the best harvest age for edamame plants is 72 HST with a potential yield of 16.38 ton.ha-1, a texture value of 4.07±0.06 kg50mm.-1 and a damage level of 2.89±1.40 g . Keywords: Physical quality, edamame quality, edamame production.